Formative Strategies in Permanent Educational and knowledge production in the interface of Solidarity Economy and Mental Health (Research, Society and Development, 2022)
In 2004, Permanent Education in Health gained prominence as a public policy in Brazil. In turn, the national mental health policy avouch the labor inclusion of people with mental desorder as one of its objectives. Thus, initiatives guided by the principles of Solidarity Economy have been developed in Brazil. Still, health professionals and the workers of this initiatives have been joining forces with Universities, associations, etc. configuring Solidarity Economy and Mental Health networks, with the objective of generating work and enlarge the income. As a confluence, the aim of this article is to present reflections on Permanent Education in Health, based on the description of formation actions carried out by two of these networks. Thus, the qualitative research “Solidary Economy Networks: potential, barriers and strategies” was developed. Structured by the action research method, with data collection based on interviews, carried out with key people related to one of the studied networks, and on field diary notes of the participation in the meetings and actions developed by two of this networks. As results, we highlight: the importance of networks for the development of formation actions in health; the need to transpose the hierarchical and technicist notion, frequently present in Permanent Education in Health, in order to promote spaces, in which dialogic and democratic community meetings can be established and (re)configure work processes. Still, the importance of actions that promotes reflexive formations that leads to the (re)construction of public policies was emphasized.